HUBUNGAN TINGKAT PENGETAHUAN KESEHATAN REPRODUKSI DENGAN KEHAMILAN PRANIKAH PADA IBU YANG MENIKAH USIA MUDA DI KECAMATAN MUARA PINANG - Suhita Tri Oklaini (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2022)
Marriage in early age is often caused by pregnancy out of marriage. Pregnancy in adolescent if they are not able to accept these changes will experience psychological disorders that result in the pregnancy being a risk of pregnancy. The aims of this study was to determine Relationship between knowledge level of reproductive health with premarital pregnancy among Early Marriage mothers in Muara Pinang District, Empat Lawang Regency. This study was an analytical survey with a Cross Sectional approach. Sampling technique in this study uses total sampling technique with a total sample of 33 respondents. Data collection uses a questionnaire was carried out by home visits. by implementing the Covid-19 protocol. Data analysis uses chi-square statistical test. The results of this study were: 1) there were 18 respondents with lack of knowledge, there were 9 respondents had moderate knowledge and there were 6 respondents with good knowledge, 2) there were 22 respondents with premarital pregnancy and there were 11 respondents did not have premarital pregnancy, 3) there is significant Relationship between knowledge level of reproductive health with premarital pregnancy among Early Marriage mothers in Muara Pinang District, Empat Lawang Regency with moderate relationship. It is hoped that the sub-district can collaborate with Puskesmas to activate the Posyandu so that it can share reproductive health information. Keywords: Premarital Pregnancy, Knowledge